Women in ministry : four views - Clouse, Bonnidell; Clouse, Robert G., 1931-; Culver, Robert Duncan (Downers Grove, Illinois InterVarsity Press, 1989)
Should women teach men? Should they exercise authority over men? What about ordaining women? Even those who agree that scripture must determine our answers do not agree on what it teaches. And too often differing sides have not been willing to listen to one another. Here in one volume are the views of four deeply committed evangelicals that focus the discussion on the issues. Robert Culver argues for what might be called the traditional view that women should not exercise authority over or teach men. Susan Foh suggests a modified view which would allow for women to teach but not to hold positions of authority. Walter Liefeld presents a case for plural ministry that questions ordination as a means of conferring authority. Alvera Mickelsen defends the full equality of men and women in the church. What makes this book especially helpful is that the writers all respond to the other essays, pointing out weaknesses and hidden assumptions. - Back cover.
Robert Culver argues for what might be called the traditional view that women should not exercise authority over or teach men. Susan Foh suggests a modified view which would allow for women to teach but not to hold positions of authority. Walter Liefeld presents a case for plural ministry that questions ordination as a means of conferring authority. Alvera Mickelsen defends the full equality of men and women in the church.
1. A traditional view. Let your women keep silence / Robert D. Culver -- A male leadership response / Susan T. Foh -- A plural ministry response / Walter L. Liefeld --
Includes bibliographical references.
"Select bibliography": pages 241-247.
Keywords: Women clergy; Sex role -- Religious aspects -- Christianity